Feasible elimination procedures in social choice: An axiomatic characterization. Issue 1 (March 2017) - Peleg, Bezalel; Peters, Hans
Abstract: Feasible elimination procedures (Peleg, 1978 ) play a central role in constructing social choice functions which have the following property: in the associated game form, for any preference profile there exists a strong Nash equilibrium resulting in the sincere outcome. In this paper we provide an axiomatic characterization of the social choice correspondences resulting from applying feasible elimination procedures. The axioms are anonymity, Maskin monotonicity, and independent blocking. We also show that these axioms are logically independent.